JIHAD DAN TERORISME KAJIAN FIKIH KONTEMPORER - Mathar, M. Saleh (Institut Agama Islam Negeri (IAIN) Palu, 2009)
This article discusses jihÃ¢d and terrorism based on contemporary fiqh perspective. JihÃ¢d has an important meaning in Islamic teaching as a part of religious obligation. However, nowadays the word jihÃ¢d has been associated with the term terrorism by Western World. In fact, terrorism is completely different from Islamic spirit (jihÃ¢d). Therefore, this article tries to reveal the differences between jihÃ¢d and terrorism. This issue is discussed by employing contemporary fiqh perspective approach. The result shows that jihÃ¢d and terrorism are totally different from each other. JihÃ¢d has the criteria which are stated in Islamic sharâiah, while terrorism is a form of movement against the Islamic teaching.Kata Kunci: jihad, terorisme, syariah, sadd Â al-tharÃ¢âi